Impact of etiology and duration of pain on pharmacological treatment effects in painful polyneuropathy. (30th May 2017) - Sindrup, S. H.; Holbech, J.; Demant, D.; Finnerup, N. B.; Bach, F. W.; Jensen, T. S.
Abstract: Background: The pharmacological treatments for painful polyneuropathy have not changed much for more than a decade, and less than half of the patients obtain adequate pain relief with first line treatments. Therefore, patient‐specific factors which could predict drug response are searched for. Methods: We analysed data from four published, randomized, controlled trials of drugs in painful polyneuropathy to see if diabetic etiology and duration of neuropathic pain had an impact on drug efficacy. The studies had a cross‐over design, and had nearly similar outcome recordings as well as a thorough baseline registration of symptoms, signs and quantitative sensory testing. 244 patient records of drug effect distributed over treatments with three antidepressants (imipramine, venlafaxine, escitalopram) and two anticonvulsants (pregabalin, oxcarbazepine) were analysed. Results: Diabetes as etiology of polyneuropathy had no impact on the effect of antidepressants (imipramine, venlafaxine, escitalopram), but there was a significant interaction with treatment effect on anticonvulsants with better effects in diabetics (0.86 NRS points, p  = 0.021) with most pronounced interaction for oxcarbazepine (1.47 NRS points, p  = 0.032). There was an interaction between duration of neuropathic pain and treatment with antidepressants with better effect with duration less than 3 years (0.62 NRS points, p  = 0.036), whereas anticonvulsants tended to work best with duration of pain for more than 3 years. Conclusion: Despite the small sample size and limited number of drugs included this study suggests that diabetic etiology of polyneuropathy may impact on the efficacy of anticonvulsants, and duration of neuropathic pain may impact on the efficacy of antidepressants. Significance: This study found that duration of pain appears to have an impact on the effect of antidepressants in neuropathic pain and that diabetes as etiology for painful polyneuropathy appears to influence pain relief obtained with anticonvulsants.